Low-Complexity Alternatives to the Optimal Linear Coding Scheme for Transmitting ARMA Sources - Gutiérrez-Gutiérrez, Jesús; Villar-Rosety, Fernando M.; Insausti, Xabier; Zárraga-Rodríguez, Marta (Entropy (Basel, Switzerland), 2022)
In the era of the Internet of Things, there are many applications where numerous devices are deployed to acquire information and send it to analyse the data and make informed decisions. In these applications, the power consumption and price of the devices are often an issue. In this work, analog coding schemes are considered, so that an ADC is not needed, allowing the size and power consumption of the devices to be reduced. In addition, linear and DFT-based transmission schemes are proposed, so that the complexity of the operations involved is lowered, thus reducing the requirements in terms of processing capacity and the price of the hardware. The proposed schemes are proved to be asymptotically optimal among the linear ones for WSS, MA, AR and ARMA sources.